Structure, conduct and performance of maize markets in Malawi: Synopsis - Ochieng, Dennis O.; Botha, Rosemary; Baulch, Bob (International Food Policy Research Institute, 2019)
This policy note summarizes Working Paper 29 (Ochieng et al., 2019), which investigates the SCP of Malawi’s maize market during the 2018/19 main marketing and lean seasons and provides policy suggestions on how to improve Malawi’s maize marketing system.